THE EFFECT OF STRATEGY COMPETENCY AND WORK MOTIVATION ON ORGANIZATIONAL PERFORMANCE OF ARMY HEADQUARTERS MEDIATED BY ORGANIZATIONAL COMMITMENT - Junaedi, Erwin; Z Basri, Yuzwar; Kusnadi (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of this study is to provide input to the leadership of the Indonesian Army National Armed Forces Headquarters regarding the importance of improving Human Resources through increasing good Work Motivation and applicable Competency Strategy order to produce good Organizational Commitment and Organizational Performance to support the success of the National Army Headquarters. Indonesian Army, especially in the General Section of the Indonesian Army National Army The design/design and research method used in this research is hypothesis testing. This research is a quantitative non-experimental, using a questionnaire given to 95 respondents. This research was conducted at the Indonesian Army National Army Headquarters. Data analysis using SPSS and PLS.3.20 software with multivariate Structural Equation Model (SEM) analysis method. The results of this study indicate that: The influence of Strategic Competency, Work Motivation on Organizational Commitment is positive and significant. The effect of Organizational Commitment on Organizational Performance is positive and significant. The effect of Organizational Commitment mediating Strategic Competency, Work Motivation on Organizational Performance is positive and significant. It means that the higher/positive mediation of Organizational Commitment to Strategic Competency, Work Motivation, the higher/positive Organizational Performance. Theoretical implications: Organizational Commitment as a mediating of Strategic Competency, Work Motivation can able to improve Organizational Performance, by increasing Organizational Commitment through increasing its dimensions will be able to improve Organizational Performance of the General Section of the Indonesian National Army, Inspectorate General of the Indonesian Army, National Army Personnel Staff Indonesian Army. Logistics Staff of the Indonesian Army National Army, Planning and Budgeting Staff of the Indonesian Army’s National Armed Forces